2023
DOI: 10.1002/dvdy.576
|View full text |Cite
|
Sign up to set email alerts
|

Canonical and non‐canonical functions of STAT in germline stem cell maintenance

Abstract: Background Maintenance of the Drosophila male germline stem cells (GSCs) requires activation of the Janus kinase/signal transducer and activators of transcription (JAK/STAT) pathway by niche signals. The precise role of JAK/STAT signaling in GSC maintenance, however, remains incompletely understood. Results Here, we show that, GSC maintenance requires both canonical and non‐canonical JAK/STAT signaling, in which unphosphorylated STAT (uSTAT) maintains heterochromatin stability by binding to heterochromatin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…10 In contrast, in GSCs with sustained Upd stimulation, this mutation led to a 2.5-fold elevated uSTAT level to 24.6 nM at steady state, despite a similar initial decrease (Figure 5B), consistent with the observed higher uSTAT levels heterochromatin levels in GSCs. 32 GSCs having higher levels of uSTAT, as detected by antibodies against total STAT, have been previously reported. [38][39][40] Alternatively, the hop Tum-l mutation could lead to constitutive activation of JAK regardless of Upd stimulation.…”
Section: Effects Of Jak Mutations On the System Outputmentioning
confidence: 58%
See 4 more Smart Citations
“…10 In contrast, in GSCs with sustained Upd stimulation, this mutation led to a 2.5-fold elevated uSTAT level to 24.6 nM at steady state, despite a similar initial decrease (Figure 5B), consistent with the observed higher uSTAT levels heterochromatin levels in GSCs. 32 GSCs having higher levels of uSTAT, as detected by antibodies against total STAT, have been previously reported. [38][39][40] Alternatively, the hop Tum-l mutation could lead to constitutive activation of JAK regardless of Upd stimulation.…”
Section: Effects Of Jak Mutations On the System Outputmentioning
confidence: 58%
“…23,29,[38][39][40] It has been previously shown that both canonical and noncanonical functions of JAK/STAT signaling in GSCs are important for GSC maintenance. 32 Moreover, it has been shown that the central heterochromatin components such as HP1 and Su(var)3-9 methyltransferase are required for GSC maintenance 41 and that GSCs have higher levels of heterochromatin, which is regulated by the non-canonical STAT function. Further, both HP1 and STAT are among the transcription targets of canonical JAK/STAT signaling in GSCs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations